HUBUNGAN PENGGUNAAN JENIS MEDIA MASSA DENGAN KEJADIAN DATING VIOLENCE - Satriyandari, Yekti; Oktaviani, Mur (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstrack: The study aimed to determine the correlation between the use of mass media and dating violence occurrence at State Senior High School 1 Pajangan Bantul Yogyakarta. The correlation study used cross sectional approach. Samples were 108 students (total sampling). The measuring instruments were checklists and questionnaires. The data were analyzed using Chi Square. That was indicated by the value x 2 (12.531) with the significant value (p = 0.002 <0.05), and the contingency coefficient (0,322). There was a correlation between the use of mass media and dating violence occurrence at State Senior High School 1 Pajangan Bantul Yogyakarta. It is expected that teenagers do not date in order to avoid the incidence of dating violence and are able to use information technology properly and appropriately.Keywords: the use of mass media, dating violence